The Research-Practice Psychotherapy Wars: The Case of Group Psychotherapy in the Treatment of PTSD. Issue 3 (3rd July 2021) - Greene, Les R.
ABSTRACT: In light of two recent meta-analyses of the efficacy of group psychotherapy in treating posttraumatic stress disorder (PTSD), this article critically reviews the randomized control trial (RCT) generated findings as well as two of its outgrowths—the production of a variety of clinical practice guidelines for treating PTSD and the dissemination efforts to transfer laboratory findings to clinical practice. All three of these activities have received considerable pushback from experienced clinicians and Boulder-identified scientist practitioners, creating an ongoing and entrenched gap or split between researcher and clinician. The article also reviews the various suggestions that have been offered to heal this gap and ending the hegemony of RCT outcome research as the only game in town for declaring what constitutes evidence. Specifically, the literature suggests two primary strategies for helping to realize the scientist-practitioner model and thus advancing the cause of psychotherapy, in general, and group psychotherapy, in particular: (a) leveling the playing field so that both researcher and practitioner have real authority and voices for shaping the field; and (b) shifting the research priority away from a purely outcome focus, asking only does it work, and moving to a more sophisticated, theoretically guided empirical study of process-outcome, examining the how, why, when, and for whom it works.